How Much Is Too Much? Examining the Relationship Between Digital Screen Engagement and Psychosocial Functioning in a Confirmatory Cohort Study - Przybylski, Andrew K; Orben, Amy; Weinstein, Netta (Journal of the American Academy of Child and Adolescent Psychiatry, 2020)
Previous studies have offered mixed results regarding the link between digital screen engagement and the psychosocial functioning of young people. In this study, we aimed to determine the magnitude of this relation, to inform the discussion regarding whether amount of digital screen time has a subjectively significant impact on the psychosocial functioning of children and adolescents. We analyzed data from primary caregivers participating in the National Survey of Children's Health (NSCH), an annual nationally representative survey fielded by the US Census Bureau between June 2016 and February 2017. NSCH uses an address-based sampling frame and both Web- and paper-based data collection instruments to measure psychosocial functioning and digital engagement, including a modified version of the Strengths and Difficulties questionnaire and caregiver estimates of daily television- and device-based engagement, respectively. The expected parabolic inverted-U-shaped relationship linking digital screen engagement to psychosocial functioning was found. These results replicated past findings suggesting that moderate levels of screen time (1-2 hours a day) were associated with slightly higher levels of psychosocial functioning compared to lower or higher levels of engagement. Furthermore, it indicated that children and adolescents would require 4 hours 40 minutes of television-based engagement and 5 hours 8 minutes of daily device-based engagement before caregivers would be able to notice subjectively significant variations in psychosocial functioning. The possible influence of digital screen engagement is likely smaller and more nuanced than we might expect. These findings do not rule out the possibility that parents might only notice very high levels of screen time when their child manifests pronounced psychosocial difficulties. Future work should be guided by transparent and confirmatory programs of research.